Simulasi Kebakaran Hutan dan Lahan di Provinsi Riau Menggunakan Cellular Automata - Roni Al Maududi; Rini Widia Putri Z (Journal of Science and Technology, 2022)
One of the causes of the large number of forest and land fires in Riau Province is human intent to divert forest functions, so that hotspots appear in areas that have the potential for forest and land fires. The purpose of this study was to simulate forest and land fires that occurred in Riau Province using Cellular Automata by utilizing satellite imagery. Land in Riau Province is divided into 5 states, namely: dry land, wet land, land that is being burned, land that has been burned, and land of water. The method used for simulating forest fires is the Cellular Automata to simulate the movement of fire during a fire. This method is able to explain the pattern of fire spread of the main cell fire from neighboring cells. At the end of the study, the simulation results and the movement of fire from where the hotspots appear on satellite images of Riau Province will be shown according to the state of the land cover. The results of this study are a description of the real situation of fires that occurred in Riau Province based on the emergence of hotspots and their movement patterns.